Aménager la berge en rive droite de la Loire à l’époque romaine à Orléans/Cenabum (Loiret) - Julien Courtois; Émilie Roux-Capron (Gallia)
The commercial character of the ancient city of Orléans/Cenabum, mentioned in the texts and known from archaeological traces, is well established for the Iron Age and then for the Early Roman Imperial period. Several preventive archaeological operations provide a series of data that make it possible to imagine a restoration of the river banks throughout the Roman period. The banks of the Loire river have thus been constantly developed, transformed and modified to encourage urbanisation, to ensure bank stability and to facilitate the loading and unloading of goods from boats sailing on the river. From the end of the Late Iron Age the banks were developed by the creation of embankments encroaching on the river. This technique of reinforcing the banks by adding embankments was widely implemented during the Early Roman Imperial period, with quays or landing stages being created by alignments of piles designed to support the artificial banks. Within a century, between the end of the 1st c. BC and the end of the 1st c. AD, successive quays made it possible to gain almost 30 m of land along the Loire river. These massive additions of embankment created vast open spaces between the river and the city. These took the form of level ground, sometimes even streets, along the banks, allowing traffic to flow along the river banks and to access them from the city. Set back from these open spaces were several semi-subterranean masonry buildings. This group of buildings, directly linked to the adjacent port structures (developed bank and open-air loading space), could be interpreted as a series of warehouses. From the second half of the 4th c. AD and the construction of the castrum the direct link between the river banks and the city was broken, but it seems likely that one or more posterns allowed access to the banks. In fact, the construction of the southern section of the enclosure pushed the banks several dozen metres back south of the developments dated to the 1st c. AD, immobilising the banks of the river for almost a millennium after two to three centuries of gradual land gain along the course of the Loire river1.